Performance Evaluation and Optimal Management of Mode 2 V2X Communications in 5G Networks - Gonzalez, Edgar E.; Estrada, Yanet; Garcia-Roger, David; Monserrat, Jose F. (IEEE access, 2023)
New Radio (NR) Vehicle-to-Everything (V2X) communications, a subject of the Third Generation Partnership Project (3GPP) specifications for 5G networks, enable vehicle communications akin to Long Term Evolution (LTE). These communications can be implemented either centrally, by connecting to 5G nodes, or autonomously, by establishing sidelink through the PC5 interface. Particularly noteworthy is the latter connection mode, referred to as Mode 2, which is independent of cellular network coverage. Instead, communication is established using pre-configured parameters and a sensing mechanism for resource selection and allocation in time and frequency. This paper delineates the resource selection procedures for NR VV2X Mode 2 and evaluates their performance across various scenarios. The findings suggest superior performance of high numerologies compared to smaller subcarrier spacings. Even though the standard prescribes a random method for V2X resource selection, it was observed that the sensing procedures yield higher Packet Reception Ratio (PRR) levels. Moreover, factors such as a smaller sidelink channel size and an extended duration of the candidate resource sensing window were found to enhance the frequency diversification of resources, thereby improving PRR levels. A qualitative examination of key considerations for the performance evaluation of Radio Access Technologies (RAT) V2X communications is also provided, delving into aspects such as RAT interplay, resource utilization, interoperability, performance trade-offs, and Quality of Service (QoS) for optimal management of multi-RAT V2X scenarios.